Enhanced solubilization of curcumin in mixed surfactant vesicles. (15th May 2016) - Kumar, Arun; Kaur, Gurpreet; Kansal, S.K.; Chaudhary, Ganga Ram; Mehta, S.K.
Highlights: Critical aggregation concentrations of mixed cationic surfactants have been observed. Solubility and stability of curcumin is efficiently enhanced. Radical scavenging activity of curcumin has been significantly improved. Non-uniform distribution of the curcumin in mixed vesicle has been observed. DNA and mixed surfactant interaction non-intercalative mode. Abstract: Self-assemblies of equimolar double and single chain mixed ionic surfactants, with increasing numbers of carbon atoms of double chain surfactant, were analyzed on the basis of fluorescence and conductivity results. Attempts were also made to enhance the solubilization of curcumin in aqueous equimolar mixed surfactant systems. Mixed surfactant assembly was successful in retarding the degradation of curcumin in alkaline media (only 25–28 40% degraded in 10 h at pH 13). Fluorescence spectroscopy and fluorescence quenching methods were employed to predict the binding position and mechanism of curcumin with self-assemblies. Results indicate that the interactions take place according to both dynamic and static quenching mechanisms and curcumin was distributed in a palisade layer of mixed aggregates. Antioxidant activity (using DPPH radical) and biocompatibility (using calf-thymus DNA) of curcumin-loaded mixed surfactant formulations were also evaluated. The prepared systems improved the stability, solubility and antioxidant activity of curcumin and additionally are biocompatible.